Genotype X environment interaction analysis on dry biomass yield of late maturing fodder oat (Avena sativa L.) genotypes in mid and highland areas of West Arsi and Bale, South East Ethiopia - Kedu, Aliyi; Lencho, Gemechis; Tesfaye, Wubshet; Wegi, Teklu (Journal of Scientific Agriculture, 2025)
Eleven genotypes of fodder Oat (Avena sativa L.) were evaluated across four locations with one standard checks Bona-bas under rainfall conditions from 2022 to 2023. Both agronomic and chemical composition data were collected. The analysis of the data indicated a statistically significant difference(P<0.05) between genotypes in the days of 50% heading, plant height, biomass yield, date to seed maturity, thousand kernel weight and seed yield. The overall mean of Biomass yield (15.8 ton ha-1) and Seed yield (29.3 quint ha-1). Quality parameters such as ash, crude protein(CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL) and dry matter content is not significantly different (P>0.05) between genotypes. The additive main effects and multiplicative interaction (AMMI) analysis of the dry Biomass yield indicated significant influence by genotype, Environment and year interaction. Among the Eleven genotypes and Bona-bass standard check evaluated in the trial the ILRI #5427 and ILRI #5524 has indicated higher biomass yield and Better stability were selected for variety registration and further promotion.